Diseño y construcción de una troqueladora manual para la producción de partes en cuero de tarjeteros. (2020)
In the textile industry of leather goods and leather, leather processing with the aim of designing and manufacturing new, more sophisticated tools, with greater aesthetic acuity and excellent quality, has been at the forefront. In small and medium-sized companies whose manufacturing processes include leather, the manufacture of new tools with this material is based manually or with low-performance mechanical machines. Supported in the economic investment of the small companies, in the contributing quality and in the execution times in the manufacturing operation of leather parts, a manual punching machine has been designed with engineering standards tested by construction. This machine has the objective of facilitating work in the leather industry, giving small and medium-sized companies a solution to efficiency, with low amounts of investment in their construction and considerably improving the quality of manufactured parts. This project is constituted in two phases: The first one is the design, whose analysis includes the memory of calculations, the planes of geometric design dimensioned and the abstract part of its manufacture. The second phase is construction, whose objective is basically to materialize the design and finally deliver a functional product, competent in the textile industry and attractive for small business owners.